Integrasi Inovasi Hijau dalam Praktik Bisnis Berkelanjutan: Tinjauan Literatur Kontekstual Indonesia - Munawir Haris; Herdian Mainaki; Najma Taralia Farah; Aldo Febrian; Ahmad Choiri (MANABIS: Jurnal Manajemen dan Bisnis, 2026)
This study aims to examine the integration of green innovation into green business practices in Indonesia through a literature review approach. The phenomenon of global climate change, combined with consumer pressure and increasingly strict regulations, demands that companies transform toward sustainability. Green innovation includes the renewal of products, processes, and business models that are environmentally friendly. This study synthesizes various scientific publications from 2016 to 2025, focusing on green strategies and sustainable business performance. The analysis shows that large companies tend to excel in adopting green technologies due to their resource support and market access, while SMEs demonstrate potential in community-based product innovation. Common challenges include limited access to financing, low environmental literacy, and inconsistent government policies. Nevertheless, opportunities for developing green innovation remain wide open, especially with cross-sector collaboration and sustainability-based incentives. This research provides both practical and theoretical contributions to strengthening a business transformation framework that is adaptive, innovation-based, and contextually relevant to the Indonesian setting.